Didactic Guidelines for the Development of a Modern Textbook - Tuychiyevna, Razikova Lola (International Journal on Orange Technologies, 2023)
The article outlines the course of research on the topic of the research work "Scientific foundations for creating a modern textbook that meets the tasks of forming schoolchildren's key skills of a person of the 21st century": the initial theoretical provisions are formulated, the methodological framework of the study is characterized, and the main directions of the study are determined. Some results of a survey of teachers, students and their parents, conducted in order to identify the ideas of the subjects of the educational process about the modern textbook, are analyzed.